[RETRACTED:] Proses Relasi Gender Pada Single Parent dalam Membentuk Identitas Gender Anak - Camelia Arni Minandar; Siti Komariah; Tutin Aryanti (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
[This article is retracted because the authors have already submitted and published it elsewhere. The authors submitted it to another journal while the article was in the editorial process of Yinyang: Jurnal Studi Islam Gender dan Anak.] [Editor-in-chief: Vivi Ariyanti] ****************************** The problem of the status of being a single parent who experiences a change in role and has a double burden in the formation of a child’s gender identity, becomes a separate difficulty for single parents. The formation of gender identity itself is an important part of recognizing the concept of gender as a boy (masculine) or female (feminine) which is influenced by biological, social and cognitive factors during the socialization process of their parents. To describe this situation, this research study focuses on examining how gender relations between children and single parents of different sexes provide an understanding of children’s gender identity using social learning theory. In this study, a qualitative approach was used based on a critical review of the literature, both theoretical and empirical. The results showed that, the process of forming a gender identity in the socialization stage was considered to be an imbalance in the social learning process of gender identity. The domination of gender norms when the socialization of gender identity formation obscures the role of one gender, so that the meaning of gender is considered biased. The results showed that in single parent families, there tends to be an imbalance in the social learning process of gender identity because of the vacuum of gender roles. The domination of gender norms during the socialization of gender identity formation can obscure the role of one gender, so that the meaning of gender is considered biased.